Cosmopolitan Belonging and Third Space: An Ethnographic Study of the Durham Bubble Tea Society as a Site of Cultural Identity and Transnational Belonging - Xinwei Zhang (Genealogy, 2025)
This ethnographic study explores the Durham Bubble Tea Society as a site of cultural identity and transnational belonging among university students. Through qualitative data collection, including interviews and questionnaires, this research investigates why students feel the need to establish a society centered around bubble tea, a drink with deep cultural resonance in East Asia but also a globalized product. The study identifies three overarching themes: maintaining original lifestyles amid transnational mobility, cosmopolitan aspirations and the symbolism of bubble tea, and the hybrid space of the Bubble Tea Society. These themes highlight how the society functions as a third space, bridging cultural divides and fostering transcultural connections. The findings contribute to broader theoretical discussions on transnational identity, cosmopolitan belonging, and the role of cultural artifacts in shaping globalized identities. This study underscores the importance of third spaces in fostering inclusivity and understanding, emphasizing the need for critical engagement with cultural symbols to ensure authentic cosmopolitan belonging.